PELAKSANAAN FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH TERHADAP ANGGARAN PENDAPATAN BELANJA DAERAH KABUPATEN POSO - Hidayat, Taufik (Katalogis, 2018)
This research used a qualitative research approach that describes the role and function of the local parliament in Poso regency in carrying out the direct supervision function and the indirect supervision function related to the implementation of regional budget expenditure of 2015. This research uses the supervisory function theory developed by Sondang P. Siagian (1979), namely the function of direct supervision and indirect supervision function. The local representative assembly of Poso regency in carrying out their duties and supervisory functions as set forth in Law No. 23 of 2014 have not been effectively implemented which can provide legal sanctions that have a deterrent effect on the local government of Poso Regency as implementer of public policy of regional budget expenditure of 2015. The weak role and supervisory function undertaken by the assembly of Poso regency due to juridical factor and the role of political parties factor through the fraction is more dominant political intervention on the fittings of the regional legislature. Therefore, the role and function of the oversight of the local assembly in Poso regency responded more to the findings of the corruption eradication agency of the Republic of Indonesia of Central Sulawesi and received reports from the public. This indicates that the role and function of the local assembly in Poso regency is more on administrative and political supervision. Thus, the results of this research reveal that the role and function of the local assembly of Poso regency area against the regional budget expenditure of 2015 is less effective.